Determination of extreme train running parameters along a railway line segment - Jonaitis, Jonas (Transport, 2006)
It is possible to select train‐car draft mass and traction vehicle parameters for technical speed νt along segment sk in such a way that unitary total energy consumption related to train‐car mass would be the lowest. Such running is called extreme running while traction vehicle parameters and train‐car mass are called optimal from the point of view of energy consumption. The optimization of traction vehicle parameters is possible if a mathematical traction vehicle model is added to the running program and then vehicle parameters are made variable and added to motion parameters as subsequent decision variables within train running program. Together with the train motion parameters optimization traction vehicle parameters should be optimized according to the criterion of unitary total energy consumption related to train‐car mass. Traction vehicle optimal parameters depend on train technical speed, length and profile of segment , as well as, on train‐car mass. First Published Online: 27 Oct 2010